A training module for the international course on the management and utilisation of field genebanks and in vitro collections: Held at TARI, Fengshan, Taiwan on 16 -20 May 2011 - Bioversity International; Food and Fertilizer Technology Center; Taiwan Agricultural Research Institute (2011)
The module focuses on good management practices for the conservation and utilization of material in field and in vitro genebanks. It aims to equip lecturers, practicum instructors, and technical staff in-charge of maintaining germplasm collections in field genebanks and in in vitro collections with the latest knowledge and best practices for managing these collections.This module is divided into 2 parts: lectures and discussions and practical hands-on sessions.